Westonci.ca is the best place to get answers to your questions, provided by a community of experienced and knowledgeable experts. Join our platform to connect with experts ready to provide detailed answers to your questions in various areas. Get immediate and reliable solutions to your questions from a community of experienced professionals on our platform.
Sagot :
Ok you said elimination, I included substitution and elimination, always take the easiest one, I took (Y) (8y) because it was positive, on the other equation, you can do the same, by working with the (X) (7x) because the quantity is smaller!
10= 4x-8y=
We take the (Y)=
-8 + 10y -4x=
10(-8) + 10y -4x=
2+ 10y-4=
2 - 4 + 10y
= 2+ 10y
Y= 10 -2
Y=8
10= 4x-8y=
We take the (Y)=
-8 + 10y -4x=
10(-8) + 10y -4x=
2+ 10y-4=
2 - 4 + 10y
= 2+ 10y
Y= 10 -2
Y=8
-4x + 8y = 10 ⇒ -28x + 56y = 70
7x + 9y = 19 ⇒ -28x - 36y = -76
92y = 146
92 92
y = 1²⁷/₄₆
7x + 9(1²⁷/₄₆) = 10
7x + 14¹³/₄₆ = 10
- 14¹³/₄₆ - 14¹³/₄₆
7x = -4¹³/₄₆
7 7
x = ⁻¹⁹⁷/₂₂
(x, y) = (⁻¹⁹⁷/₃₂₂, 1²⁷/₄₆)
7x + 9y = 19 ⇒ -28x - 36y = -76
92y = 146
92 92
y = 1²⁷/₄₆
7x + 9(1²⁷/₄₆) = 10
7x + 14¹³/₄₆ = 10
- 14¹³/₄₆ - 14¹³/₄₆
7x = -4¹³/₄₆
7 7
x = ⁻¹⁹⁷/₂₂
(x, y) = (⁻¹⁹⁷/₃₂₂, 1²⁷/₄₆)
We hope our answers were helpful. Return anytime for more information and answers to any other questions you may have. We hope you found what you were looking for. Feel free to revisit us for more answers and updated information. Find reliable answers at Westonci.ca. Visit us again for the latest updates and expert advice.